Sleepiness among train drivers: a case study in Malaysia - Jalil, Azlis Sani; Md Dawal, Siti Zawiah; Mohd Zakwan, Norhayati; Hasnan, Khalid (2011)
To ensure system performance and safety, train drivers need to be highly efficient. It has always been given the highest priority by all stakeholders in railway industry. Awareness and better understanding on the importance of human performance towards productivity and efficiency have increased. Monotonous driving is one of the major contributing factors for sleepiness among train drivers. The objective of the study is to determine the prevalence of sleepiness among train drivers and the importance to address sleepiness problem by the train operating companies (TOC) in Malaysia. 195 male train drivers were selected to answer self- administrated questionnaire to gather information on age and working experience. The Epworth Sleepiness Scale (ESS) was used to measure sleepiness among the train drivers; where the respondents themselves rate their chances to doze off or fall asleep in eight typically different situations. Flinders Fatigue Scale (FFS) was used to measure fatigue among the train drivers. The respondents were locomotive drivers and junior drivers from five different depots across Peninsular Malaysia; who drive locomotives in long haul operations. The results of the analysis are presented to provide better understanding on the sleep-related factors the impact on the performance of train drivers.